2001
DOI: 10.1007/s00276-001-0269-6
|View full text |Cite
|
Sign up to set email alerts
|

Double common bile duct with ectopic drainage into the stomach. Case report and review of the literature

Abstract: A rare abnormal biliary tract consisting in a double common bile duct with an ectopic biliary tree draining into the stomach is described. This congenital anomaly, associated with lithiasis in the ectopic duct, was detected for the first time on MR-cholangiopancreatography. Only 23 cases of abnormal biliary drainage into the stomach have been reported in the literature. Embryogenesis and potential risks, such as lithiasis in the ectopic duct and the development of gastric carcinoma, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…Although, we do not know the exact frequency of ectopic biliary drainage, the frequency of the ectopic biliary drainage was found to be 2% in our series. In 2001, Bernard P et al reported only 23 cases with this condition by then [9]. In the literature, there were some other small case series and when we analyzed all these cases, we noticed that they were mostly patients with double choledochus [9-12].…”
Section: Discussionmentioning
confidence: 92%
“…Although, we do not know the exact frequency of ectopic biliary drainage, the frequency of the ectopic biliary drainage was found to be 2% in our series. In 2001, Bernard P et al reported only 23 cases with this condition by then [9]. In the literature, there were some other small case series and when we analyzed all these cases, we noticed that they were mostly patients with double choledochus [9-12].…”
Section: Discussionmentioning
confidence: 92%
“…Although ectopic opening of the biliary system into the stomach via the accessory bile duct was previously reported, until recently there have been only 4 case reports of the CBD directly opening into the stomach in the literature worldwide. [15][16][17][18][19][20] The most frequently reported ectopic opening of the CBD is the opening into the duodenal bulb. This was also Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, diseases related with the biliary system are reported frequently in patients with ectopic CBD opening [2][3][4]9,[11][12][13][14][15][16][17][18]. In this study, CBD dilatation was found in 94% of the cases with or without intrahepatic biliary dilatation.…”
Section: Discussionmentioning
confidence: 57%